Effects of intravitreal connective tissue growth factor neutralizing antibody on choroidal neovascular membrane-associated subretinal fibrosis. (July 2019) - Daftarian, Narsis; Rohani, Shirin; Kanavi, Mozhgan Rezaei; Suri, Fatemeh; Mirrahimi, Mehraban; Hafezi-Moghadam, Ali; Soheili, Zahra-Soheila; Ahmadieh, Hamid
Abstract: Connective tissue growth factor (CTGF) plays an essential role in the regulation of extracellular matrix proteins and pro-fibrotic and angiogenic factors. This experimental research was conducted to evaluate if CTGF is elevated after induction of a choroidal neovascular membrane (CNVM) and whether intravitreal anti-CTGF without and with intravitreal bevacizumab (IVB) may have any effect on the CNVM associated sub-retinal fibrosis. In adherence to ARRIVE guidelines, CNVM was induced by laser spots in the right eye retinas of ninety-four pigmented rats. Quantitative real-time reverse transcription PCR (qRT-PCR) and western-blot analysis were performed on sclerochoroidal tissues of forty-four rats before and at different time intervals after laser application. The remaining fifty rats were randomly divided into five groups after laser application. Group A received intravitreal injection of 2  μl of the 50 μg/ml anti-CTGF. In group B, intravitreal injection of 2  μl of 25 mg/ml bevacizumab was performed. Group C received 1  μl intravitreal anti-CTGF and 1  μl IVB. Group D did not receive any intravitreal injection as the control group. In group E, intravitreal injection of 2  μl of nonspecific purified mouse IgG antibody was performed as the placebo group. After two weeks, double immunohistochemistry was performed by isolectin B4 and anti-collagen type1 on the sclerochoroidal flat-mounts. Masked measurement of the fluorescent images of the CNVM and CNVM associated sub-retinal fibrosis areas was performed using the image J software. Ctgf mRNA and CTGF protein levels increased to the maximum level in 24 h after laser application and remained higher than the control level up to the 14th day for the Ctgf mRNA and up to the 7th day for the CTGF protein level. Means of CNVM associated sub-retinal fibrosis areas in three treatment groups (A, B and C) were significantly less than the control (D) and placebo (E) groups (P < 0.001, <0.05, <0.001 respectively). For groups A and C, mean CNVM associated sub-retinal fibrosis areas were also significantly less than group B (P < 0.05 and < 0.01, respectively). In conclusion, this study showed significant reduction of the CNVM associated sub-retinal fibrosis via inhibition of the CTGF which mediates the final steps of fibrosis in various inflammatory and angiogenic pathways. Highlights: There was a significant increase in Ctgf mRNA level following laser-induced CNV. Intravitreal anti-CTGF decreased mean CNV vascular area in comparison to controls. Intravitreal anti-CTGF decreased mean CNV fibrosis area in comparison to controls. Intravitreal anti-CTGF decreased mean CNV fibrosis area more than anti-VEGF. Combined intravitreal anti-CTGF and anti-VEGF decreased CNV fibrosis area more than anti-VEGF alone.